OPTIMALISASI PERAN MAHASISWA KKN DALAM KEGIATAN PENGABDIAN KEPADA MASYARAKAT DI DESA KOTARAYA TIMUR - Ayu Kadek Ari Noviani, Ni Gusti; Raditya Witamo, I Made; Swuanderi, Ketut; Nina Kusumayanti, Ni Luh; Subudiani, Ni Komang; Metzvioleta, Metzvioleta; Rianto, Rianto; Mardana Yuda, I Wayan; Yasini, Ketut; Sudarsana, Wayan; Diva Pari Sangga, Gusti Gede (LPPM ITB AAS Indonesia Surakarta, 2024)
Integrated KKN STAH Dharma Sentana Central Sulawesi in Kotaraya Timur Village, Mepanga District, Parigi Moutong Regency is a form of community service activity carried out by students. KKN will be held from August 30, 2024 to November 30, 2024, consisting of several work programs, namely core work programs, sub-districts, villages, and additional programs. KKN activities aim to provide opportunities for students to apply the knowledge, technology, and skills acquired during lectures in real life, especially in the community. The KKN implementation method consists of a participatory approach, surveys, and work program planning. KKN student activities receive appreciation and support from the local government and the village community. This is shown in the KKN student activities which involve many people from various backgrounds. The village government and the community involve many KKN students in various village activities such as making street name markers, hamlet boundaries, youth health posts, and GERMAS. Other forms of work program activities involve young people, teenagers and children, such as Galungan and Kuningan holiday competitions, Sanskrit language lessons, reading, writing and arithmetic lessons, as well as holding Pasraman Kilat for all school levels from elementary, middle, high school, education to the Javanese Hindu community, and social service.